# How do you solve #(x-4)(x+3) = 6#?

##### 1 Answer

Feb 5, 2016

#### Explanation:

How to solve

**Step 1**: Multiple the expand and combine like terms for the left side of the equation

#(x^2-4x+3x-12)= 6#

#(x^2-x+-2) = 6#

**Step 2**-Set the equation equal to zero by subtracting both side of the equation by 6

#x^2 -x-12= 6#

#-6 " " " -6#

#=====#

#color(red)(x^2 -x -18= 0#

**Step 3** Solve the equation using quadratic formula, since we can't factor it

Recall: **Quadratic formula:**

#color(red)(x^2 -x -18= 0#

Substitute into the quadratic formula, we get

#x= (1+-sqrt(1+72))/(2)#

#x= (1+-sqrt(73))/2#